Peranan Cerita Rakyat Dalam Mempromosikan Daya Tarik Wisata Melalui Storytelling - Suyasa, I Made; Anggratyas, Putu Arya Reksa (IAHN Gde Pudja Mataram, 2025)
This study aims to analyze the strategic role of folklore as an instrument in promoting tourism destinations through storytelling approaches within the framework of Cultural Tourism Communication. Tourism destinations are increasingly selling not merely natural beauty or infrastructure, but also profound